The Association of Intraocular Pressure with Vitamin D Levels and Bone Mineral Density in Postmenopausal Osteoporosis - Mehmet Uçar; Ümit Sarp; Kadir Kırboğa; Mehmet Adam; Hasan Onur Arık (Galenos Yayinevi, 2015)
Objective: To investigate the effects of osteoporosis (OP) and vitamin D level on intraocular pressure (IOP) and to determine whether those constitute a risk factor for glaucoma. Materials and Methods: Eighty postmenopausal patients with the diagnosis of OP (group 1) and 74 controls (group 2) were included in the study. Age, height, weight and body mass index (BMI) of the patients were recorded. Bone mineral density (BMD) was measured from the lumbar vertebrae and proximal femur by using dual-energy x-ray absorptiometry (Lunar DPX-IQ®). The levels of 25(OH)-vitamin D were measured. Visual acuity was assessed by using Snellen charts. Gonioscopy was performed following the examination of the anterior segment with biomicroscopy. Applanation tonometry was used to measure the IOP at the same daytime. Dilated fundus examination was performed after applying 1% tropicamide eye drops. Results: The mean age of the patients in group 1 and 2 were 62.4±10.5 and 60.6±11.9 years, respectively. Although the IOPs were higher in the group 1, the results were not statistically different (p>0.05). The difference between the levels of vitamin D were not statistically significant (p>0.05). There was a strong negative correlation between IOP and vitamin D (p=0.003, r=0.428). No correlations were found between BMD, lumbar vertebral and femoral T-scores and IOP (p>0.05)Conclusions: The results of this study suggest that OP does not affect the IOP, but deficiency of vitamin D may be a risk factor for higher IOPs. Thus, it can be recommended that vitamin D supplement may be useful in decreasing the higher IOP which is an important risk factor for glaucoma. In the prevention of osteoporotic fractures related to falls routine ocular examination and measurement of IOP should be performed. (Turkish Journal of Osteoporosis 2015;21: 1-4)